1990
DOI: 10.1161/01.atv.10.4.564
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal antibodies against formaldehyde-modified apolipoprotein A-I. An approach to circumventing fixation-induced loss of antigenicity in immunocytochemistry.

Abstract: A central requirement for the subcellular localization of synthesized and/or endocytozed llpoproteins Is the availability of antibodies against the antigen to be localized. The preparation of cells for electron microscopy, In particular the fixation and embedding routine, Influences the antigenicity, often resulting In a markedly reduced labeling intensity. To ameliorate fixation-Induced changes in antigenicity, we produced antibodies against pre-flxed human apolipoprotein (apo) A-l. Purified apo A-l was fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…As in diagnostic pathology, aldehyde fixation is commonly used and although the fixation conditions can be better controlled, antibodies may fail to recognize their respective antigens. Thus, polyclonal antibodies were raised against the formaldehyde-treated antigen to improve their reactivity toward formaldehyde-exposed cellular components (Harrach and Robeneck 1990). Brown and colleagues (1996) pointed out that some antibodies may produce excellent results when applied for immunoblotting, but no or only variable staining if used for immunocytochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…As in diagnostic pathology, aldehyde fixation is commonly used and although the fixation conditions can be better controlled, antibodies may fail to recognize their respective antigens. Thus, polyclonal antibodies were raised against the formaldehyde-treated antigen to improve their reactivity toward formaldehyde-exposed cellular components (Harrach and Robeneck 1990). Brown and colleagues (1996) pointed out that some antibodies may produce excellent results when applied for immunoblotting, but no or only variable staining if used for immunocytochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The critical importance of rendering the IHC technique suitable for routine paraffin sections was pointed out by Taylor and Burns (1974). The utility of IHC in surgical pathology increased with the use of enzyme digestion (Huang 1975), other pretreatments for unmasking antigens (Kitamoto et al 1987;Hausen and Dreyer 1982;Elias and Johnsen 1979), and the development of antibodies against formalin-modified antigens Harrach and Robenek 1990). However, the use of many antibodies for routinely processed paraffin sections continued to be limited in spite of these enhancement techniques and improvements in the detection system (Leong et al 1988).…”
mentioning
confidence: 99%
“…Since it is generally impracticable to avoid these fixation-induced changes of antigenicity, we have tried to improve the lipoprotein/apolipoprotein recognition in fixed tissues by chemically modifying the lipoproteins/apolipoproteins with formaldehyde before immunization. Harrach and Robenek 26 have demonstrated that antibodies against formaldehyde-fixed lipoproteins/apolipoproteins are more appropriate than are antibodies against unmodified lipoproteins/apolipoproteins for localization in fixed samples. The present study revealed that the antibodies generated against prefixed LDL are more appropriate because they exhibit a higher specificity and a lower background labeling on the tissue sections as well as on ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…26 Another polyclonal antibody to formaldehyde-fixed LDL (anti-fix LDL-D) raised in the rabbit was kindly provided by Dr. H. Dieplinger, University of Innsbruck, Innsbruck, Austria. For the characterization of SMCs in the arteriosclerotic plaques, we used the mouse monoclonal antibody asm-1 raised to a-actin of SMCs (anti-SMC), which was purchased from Progen, Heidelberg, FRG.…”
Section: Antibodiesmentioning
confidence: 99%